DESIGN AND EVALUATION OF A CONSTRUCT 3-BASED EDUCATIONAL GAME TO PROMOTE LEARNING ON SDG 7: AFFORDABLE AND CLEAN ENERGY - Julietta Tsuraya Puspa Rannie; Erna Suhartini; Mustamiroh Mustamiroh; Muhlis Muhlis (JURNAL NALAR PENDIDIKAN, 2025)
This research develops a Construct 3-based educational game integrated with Sustainable Development Goal 7 (Affordable and Clean Energy) for fourth-grade elementary students, with a focus on energy materials. Employing Research and Development methodology with the ADDIE model, the study involved 27 students and one teacher at SDN 007 Samarinda Ilir. The research instruments consisted of interview sheets, needs questionnaires, expert validation forms, and user response questionnaires. Expert validation yielded 92% feasibility ratings from media specialists and 89.3% from material experts, both of which were rated as "highly feasible." Small-scale trials achieved a 97% acceptance rate, while large-scale implementation scored 94% from students and 96% from teachers, confirming excellent usability and educational value. Results demonstrate the game's effectiveness in enhancing student engagement and conceptual understanding of energy topics. The media successfully bridges theoretical learning with practical sustainability awareness, fostering students' commitment to clean energy practices. This innovation provides educators with a validated tool that simultaneously achieves curriculum objectives and fosters global citizenship values through interactive learning. The game's design provides a replicable framework for integrating other SDG targets into elementary science education, addressing critical gaps in current pedagogical approaches to sustainable development education.